ANALYSIS OF THE UNDERGROUND STRUCTURE IN THE CORAL FOUNDATION UNDER DYNAMIC LOADING - Luong, Hoang Xuan; Chung, Nguyen Thai; Ngan, Nguyen Tat (Vietnam Journal of Marine Science and Technology, 2009)
In this study, the authors present the calculating method for the underground structure in the coral foundation of Truong Sa Archipelago under dynamic loading (Blast loading) byfinite element method using slip element. By using the slip elements to bring essence true-natured ofthe coral foundation, example the opening or slip at the interface between the structure and coralfoundation. The paper results can be used in design as reference for underground structures in the coralfoundation.